RANCANG BANGUN SISTEM INFORMASI LAYANAN UMROH BERBASIS WEB PADA PELITA SAHABATKU TOUR AND TRAVEL (Information Technology and Telematics, 2015)
Abstract- Pelita My friend is a travel service that serves the trip personally help Umrah pilgrims in the planning and execution of a series of events Umrah trip in accordance with the schedule and budget that has been set. Umrah service information system Pelita FRIENDS created by utilizing web-based information technology, with the aim to expand the area of ​​promotion and simplify the                ordering process. Umrah service information system Pelita My friends using the programming language PHP and MySQL, the methods used in the development of this system is using waterfall method (analysis, design, application development, implementation, discussions, and                result). Pelita information system Umrah Services Sahabatku very helpful for pilgrims to perform the ordering process. With the development of technology today Umrah Services has begun to move from a manual process into the process online information system that is Web-based Umrah Services.